2018
DOI: 10.3390/ijms19051501
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cadmium Thyroid Disrupting Effects and Mechanisms

Abstract: Humans are exposed to a significant number of chemicals that are suspected to produce disturbances in hormone homeostasis. Hence, in recent decades, there has been a growing interest in endocrine disruptive chemicals. One of the alleged thyroid disrupting substances is cadmium (Cd), a ubiquitous toxic metal shown to act as a thyroid disruptor and carcinogen in both animals and humans. Multiple PubMed searches with core keywords were performed to identify and evaluate appropriate studies which revealed literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 115 publications
2
97
1
Order By: Relevance
“…Although several studies focused on the ability of heavy metals and POPs to alter the functionality of the endocrine system (Beszterda & Franski, 2018;Buha et al, 2018;Kranthi Kumar, Uma Devi, & Neeraja, 2018;Paschoalini, Savassi, Arantes, Rizzo, & Bazzoli, 2019;Saxena, Purchase, Mulla, Saratale, & Bharagava, 2020), their involvement in cancer development is also increasingly emerging (Cao, Fan, Li, & Xiao, 2019;Leng et al, 2016;Rehman, Fatima, Waheed, & Akash, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies focused on the ability of heavy metals and POPs to alter the functionality of the endocrine system (Beszterda & Franski, 2018;Buha et al, 2018;Kranthi Kumar, Uma Devi, & Neeraja, 2018;Paschoalini, Savassi, Arantes, Rizzo, & Bazzoli, 2019;Saxena, Purchase, Mulla, Saratale, & Bharagava, 2020), their involvement in cancer development is also increasingly emerging (Cao, Fan, Li, & Xiao, 2019;Leng et al, 2016;Rehman, Fatima, Waheed, & Akash, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the already identified and well-established chemicals with endocrine-disrupting properties include organochlorine pesticides, polybrominated diphenyl ethers, polychlorinated biphenyls, toxic metals, as well as phthalates and bisphenol A [1,[20][21][22][23]. The results from a recent nation-wide survey of the levels of environmental contaminants among pregnant women in France showed that these chemicals are quantifiable in virtually all individuals [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the importance of miRNAs in cancer development has increased over the last few decades. The International Agency for Cancer Research (IARC) has classified Cd as a human carcinogen with a well-established association to kidney and prostatic cancers [62] as well as considerable involvement in other cancers, such as pancreatic cancer [63][64][65] and thyroid cancer [66], among which the role of miRNA in Cd-induced carcinogenesis is of great value. Evidence supporting the toxic metal modification of miRNA expression and cancer development is increasing, with Cd and As being two primary mediators [60,67].…”
Section: Cadmium-associated Changes In Mirna Expressionmentioning
confidence: 99%